Analysis of the Effect of Increasing the GDP of Central Java Province Through Infrastructure Development - Desy Rinika; Jeffri Winardy; Jerly Engelina; Arvin Clarence (Green Publisher Indonesia, 2021)
Infrastructure can be said to be the main driver for the growth of economic activity in every country in the world, therefore the importance of infrastructure cannot be underestimated. However, infrastructure development for Central Java is considered to be still in its early stages and as such, inadequate infrastructure could seriously hamper the economy. This study aims to investigate the effect that an increase in GDP has on infrastructure growth through data collected from various sources. The methodology used to analyze and review the information generated by the data is a quantitative method. The data used is secondary data on infrastructure in 35 districts in Central Java from 2010 to 2020. The analytical tool used in this study is panel data regression using the fixed effect method. Indicators to determine the progress of the national economy can be seen from the values seen in various GRDP in Indonesia. The results of this study conclude that the COVID-19 pandemic has affected several things, one of which is the country's economic growth. Planned infrastructure development can bring growth to the economy of a region as in the example shown above. Infrastructure development is one of the supporting factors to increase economic growth in a region. The development can be in the form of the establishment of hospitals, transportation facilities, public schools and other.